Air Born Bacteria Evaluation in The Kitchen Air of Restaurants in Babol City - Fatemeh Asgharzadeh; Majid kermani; Ahmad Jonidi Jafari; Sayede Sammane Taheri Otaghsara; Zahra Geraili (علوم بهداشتی ایران)
Background and purpose: Bioaerosols enter into human body through various ways (inhalation, ingestion or skin absorption). The aim of this study was to investigate the type and density of the predominant bacteria in two seasons - cold and warm - in the kitchen air of restaurants. Materials and Methods: This descriptive cross-sectional study was conducted on the air of restaurants' kitchen in Babol. Sampling was performed by using a personal sampling pump with impinger tank using a flow rate of 4 l/min during 50 minutes. Counting the colonies in the air was determined in terms of CFU/m3 and the type of grown bacteria was identified using different tests, such as Gram staining and biochemical methods. Temperature and humidity were recorded at the time of sampling, too. Totally, 120 samples of bacteria were taken from the indoor air of kitchens with and without air conditioning. Results: The results showed that the highest and lowest densities of bacteria in cold season were 15 CFU/m3 and 63.7 CFU/m3, and in warm season, they were 19.6 CFU/m3 and 80 CFU/m3, respectively. The predominant bacteria were Gram-positive bacteria in the air of kitchen but Bacillus and Micrococcus were the most frequent. Conclusion: The results showed that due to humidity and the temperature (warmer), bacterial density was higher in summer than winter. The concentration of bacteria in the kitchen and restaurant was also less than WHO recommendation and guide values ACGIH (up to 500 CFU/m3), respectively. So, air quality was found to be good and acceptable in terms of the restaurant kitchen.